O processo de desenvolvimento do enoturismo no Vale dos Vinhedos - Valduga, Vander (My University, 2014)
This study had as intention to investigate if the Wine tourism and the creation of one regional mark contributed for the intern strengthen of ´Vale dos Vinhedos` Vinhedos Valley. The study also analyzed three elements: a) wine tourism; b) invoicing and c) quality through the regional mark. The adopted paradigm was of quali-quantitative cut, serving itself of descriptive methodology. The documentary analysis and interviews had been used as instruments for all the collection of information. The participants of the research were entrepreneurs and entities that operate in the tourist promotion of the Vinhedos Valley. For the analysis, the social economies and cultural aspects of the local viticulture, the process of certification, the conquest of the indication of origin - IPVV, the wine tourism and its organization around the institutions had been studied. The ´Vale dos Vinhedos` Vinhedos Valley was colonized by Italian immigrants, who from 1876 made the viticulture the main activity developed in the territory. Although it has been identified a reduction of the participation of the population of the Vinhedos Valley in the local wine tourism, the results pointed that the process of development of the wine tourism had some similarities to other regions that had created its regional marks. It was resulted of productive specialization, the existing culture and the capacity of organization of the local agents. According to speech of the public and private managers, the certification conquered in 2002 did not incapacitate of direct form in the wine tourism, therefore it had already recognition of the product quality for the consumer before the conquest. It was also identified that the recurrent invoicing of the wine tourism motivated the new investments made in the Valley, especially in the last 5 years, beyond the creation of the regional mark and a great perspective for the future.</
Este estudo teve como propósito investigar se o enoturismo e a criação de uma marca regional contribuíram para o fortalecimento endógeno do Vale dos Vinhedos. O estudo analisou três elementos: a) enoturismo; b) faturamento; e c) qualidade através da marca regional. O paradigma adotado foi de corte quali-quantitativo servindo-se de metodologia descritiva. A análise documental e entrevistas foram usadas como instrumentos para a coleta de informações. Os participantes do estudo foram os empresários e as entidades atuantes na promoção turística do Vale dos Vinhedos. Para a análise, foram estudados os aspectos socioeconômicos e culturais da vitivinicultura local, o processo de certificação e a conquista da Indicação de Procedência - IPVV, o enoturismo e a sua organização em torno das instituições. O Vale dos Vinhedos foi colonizado por imigrantes italianos a partir de 1876, que tornaram a vitivinicultura a principal atividade desenvolvida no território. Embora tenha sido identificada uma redução da participação da população do Vale no enoturismo local, os resultados apontaram que o processo de desenvolvimento do enoturismo se deu de forma semelhante a outras regiões que criaram suas marcas regionais. Ele foi resultado de especialização produtiva, da cultura existente e da capacidade de organização dos agentes locais. Segundo o discurso dos gestores públicos e privados, a certificação conquistada em 2002 não impactou de forma direta no enoturismo, pois já havia um reconhecimento da qualidade dos produtos pelo consumidor antes da conquista. Identificou-se também que o faturamento decorrente do enoturismo motivou os novos investimentos feitos no Vale, especialmente nos últimos 05 anos, além da criação da marca regional e de uma perspectiva de futuro.
Keywords: Turismo; Enoturismo; Marca regional; Fortalecimento endógeno; Vitivinicultura; Vale dos Vinhedos; Rio Grande do Sul; Tourism; Wine tourism; Regional mark; Internal strengthen